Minat Siswa Perempuan Terhadap Ekstrakurikuler Tari Di SMK Negeri 5 Padang - Nia Rahmadani; Indrayuda Indrayuda (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study was to determine the learning interest of students in the class of SMK Negeri 5 Padang and the factors that influence students' interest in dance at SMK Negeri 5 Padang. This type of research is qualitative research with a descriptive approach. This research instrument is the researcher himself and is assisted by supporting equipment such as stationery, mobile phones and recorders. Data collection techniques through literature study, observation, interviews and documentation. The stages of exploratory analysis are data collection, data reduction, data presentation and conclusions. The lack of student interest in learning outside Dance in the material of the cultural arts teacher of SMK Negeri 5 Padang did not update the teaching material and also did not change the teaching method. Factors that influence students' interest in non-dance education at SMK Negeri 5 Padang are internal and external factors.